REFLEKSI MAHASISWA MAGISTER PENDIDIKAN AGAMA ISLAM TERHADAP PEMBELAJARAN DARING DI UNIVERSITAS ISLAM NEGERI SUNAN KALIJAGA YOGYAKARTA - Saptaputra, Idil; Hasan, Moh Ferdi; Yusuf, Muhammad Hani (Universitas Islam Madura, 2024)
Online learning is not yet very familiar among students. However, online learning is still being implemented. This research was motivated by the desire to find out the reflections of Islamic religious education master's students on online learning. This research method uses a qualitative approach with a case study strategy. Data collection through interviews, observation and documentation. The results of the research are online learning using Zoom, Google Meet, Whatsapp Group, Google Classroom, Google Meet, and SUKAmail. The challenge is adjusting the learning environment and atmosphere, as well as adjusting to the use of online learning technology. Students' perceptions regarding the positive impact of online learning are: creating technologically adept competencies, providing time and financial efficiency, parents can monitor the learning process. The negative impact is the cause of reducing the honor and dignity of lecturers as role models. The implications of this research activity are 1) improving the quality of online learning, 2) developing effective learning strategies, 3) strengthening student involvement, 4) developing educational technology infrastructure, 5) increasing lecturer competency, 6) empowering students as learning partners, 7) development of HYBRID learning, 8) preparation of online learning guidelines.